Relationships Between Stress and Psychosocial Factors with Sources of Help-Seeking Among International Students - Swanbrow Becker, Martin A.; Dong, Shengli; Kronholz, Julia; Brownson, Chris (Journal of International Students, 2018)
This study explored the prevalence of stressors and their impact on distress for international students who did not seek help, those who sought either informal or professional help, and those who accessed both informal and professional help. Results indicated that international students underutilize professional support services when faced with serious stressors, such as assaults, and often do not seek help from any source for those stressors contributing most to their overall distress. Those endorsing higher levels of belonging, sense of coherence, mindfulness, academic and social integration and their sense of connection to their university tend to turn to informal sources of support, while those with lower levels tend to turn to professional supports. Implications for prevention, outreach, and clinical practice are discussed.